2022
DOI: 10.1007/s11682-021-00604-7
|View full text |Cite
|
Sign up to set email alerts
|

Fiber connectivity density mapping in end-stage renal disease patients: a preliminary study

Abstract: Abnormal brain structural connectivity of end-stage renal disease (ESRD) is associated with cognitive impairment. However, the characteristics of cortical structural connectivity have not been investigated in ESRD patients. The current study aimed to investigate the structural connectivity of the entire cerebral cortex in ESRD patients. Twenty-ve ESRD patients and 20 healthy controls were recruited for this study; all participants underwent diffusion tensor imaging and high-resolution T1-weighted imaging scann… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…This implies that ESRD patients may have brain damage in both the left and right hemispheres to a certain degree. This is consistent with the findings we previously obtained using the fiber connectivity density (FiCD) mapping method 50 …”
Section: Results and Analysessupporting
confidence: 93%
See 2 more Smart Citations
“…This implies that ESRD patients may have brain damage in both the left and right hemispheres to a certain degree. This is consistent with the findings we previously obtained using the fiber connectivity density (FiCD) mapping method 50 …”
Section: Results and Analysessupporting
confidence: 93%
“…where W denotes the window length and Δt denotes the step size. In this study, W∈ [20,30,40,50,60], Δt∈ [1,3,5,7,9,11].…”
Section: Construction Of Low-order and High-order Functional Connecti...mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent technique named fiber connectivity density (FiCD) mapping was proposed to map the structural connectivity properties (e.g., fractional anisotropy, or mean diffusivity) to the cortical surface, to create a common space for comparison with results from brain functional analysis and cortical thickness analysis, which can automatically identify brain regions with significant differences at the whole-brain level without defining ROIs ( 18 , 19 ). Studies had shown that FiCD values were significantly changed in cerebral small-vessel disease (CSVD) patients ( 20 ) with mild cognitive impairment (MCI) and in patients with end-stage renal disease (ESRD) ( 21 ). FC can reveal brain activity, which has become an important tool in the study of neurological diseases ( 22 ), and numerous studies proved that decreased FC was related to impaired cognition in various diseases.…”
Section: Introductionmentioning
confidence: 99%